2006
DOI: 10.1103/physrevb.73.104518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhomogeneity ons-wave superconductivity in the attractive Hubbard model

Abstract: Inhomogeneous s-wave superconductivity is studied in the two-dimensional, square lattice attractive Hubbard Hamiltonian using the Bogoliubov-de Gennes (BdG) mean field approximation. We find that at weak coupling, and for densities mainly below half-filling, an inhomogeneous interaction in which the on-site interaction Ui takes on two values, Ui = 0, 2U results in a larger zero temperature pairing amplitude, and that the superconducting Tc can also be significantly increased, relative to a uniform system with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
4
35
1
Order By: Relevance
“…Unlike BCS, this Monte Carlo mean field (MCMF) approach allows identification of the weak and strong coupling regimes via the phase correlation function. In an earlier work 49 this Monte Carlo technique was employed as an independent examination for the validity of our results and the agreement between the two techniques was clearly confirmed.…”
Section: Model and Methodologysupporting
confidence: 72%
See 2 more Smart Citations
“…Unlike BCS, this Monte Carlo mean field (MCMF) approach allows identification of the weak and strong coupling regimes via the phase correlation function. In an earlier work 49 this Monte Carlo technique was employed as an independent examination for the validity of our results and the agreement between the two techniques was clearly confirmed.…”
Section: Model and Methodologysupporting
confidence: 72%
“…This model is the attractive Hubbard model, which has been applied previously to address some aspects of the impact of inhomogeneity. Recently old suggestions based on "negative U" superconductivity have been revived, 49,51 which may provide additional applications for the results we present in this paper. Tl-doped PbTe achieves a critical temperature up to 1.5 K, and more extensive heat capacity and transport data 52,53 have led to an analysis in terms of a "charge Kondo effect" that could be linked to the observed superconductivity.…”
Section: 20mentioning
confidence: 79%
See 1 more Smart Citation
“…55,56 It was shown that an exponentially decaying subgap density of states appears due to mesoscopic fluctuations which lie beyond the mean-field picture. Finally, inhomogeneous couplings in the attractive Hubbard model 57,58 and lattice XY model 59 were also analyzed, with relevance to high-T c materials.…”
Section: Introductionmentioning
confidence: 99%
“…This has been illustrated in several recent works. [3][4][5]9,10,16,[19][20][21] The main aim of this paper is to present a real-space approach to study the effect of disorder on superconductivity going beyond standard mean-field techniques for the purpose of configuration averaging. This will be based on the augmented space recursion ͑ASR͒ formalism introduced by one of us.…”
Section: Introductionmentioning
confidence: 99%